2011
DOI: 10.1002/chem.201101360
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene‐Containing Peptide‐Based Fluorescent Organogels: Inclusion of Graphene into the Organogel

Abstract: The N-terminally pyrene-conjugated oligopeptide, Py-Phe-Phe-Ala-OMe, (Py=pyrene 1-butyryl acyl) forms transparent, stable, supramolecular fluorescent organogels in various organic solvents. One of these organogels was thoroughly studied using various techniques including transmission electron microscopy (TEM), field-emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), Fourier-transform infrared (FTIR) spectroscopy, photoluminescence (PL) spectroscopy, and rheology. Unfunctionalized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 142 publications
2
114
0
1
Order By: Relevance
“…These hybrid gels are mechanically stable and solution processable. There are a few examples of graphene-containing supramolecular gels with improved properties [27][28][29][30][31][32] . For instance, it has been shown that graphene could be used as a nucleating surface to reduce the critical gelator concentration of 1 (Fig.…”
Section: Graphene and Its Derivatives With Supramolecular Gelatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These hybrid gels are mechanically stable and solution processable. There are a few examples of graphene-containing supramolecular gels with improved properties [27][28][29][30][31][32] . For instance, it has been shown that graphene could be used as a nucleating surface to reduce the critical gelator concentration of 1 (Fig.…”
Section: Graphene and Its Derivatives With Supramolecular Gelatorsmentioning
confidence: 99%
“…For instance, it has been shown that graphene could be used as a nucleating surface to reduce the critical gelator concentration of 1 (Fig. 2a) 27 . Rheological studies have revealed that the rigidity of the hybrid gel (storage Fig.…”
Section: Graphene and Its Derivatives With Supramolecular Gelatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of graphene oxide (GO) into a short peptide hydrogel improved the rigidity of the hybrid hydrogel system compared to the native one. 12 The hybrid hydrogel constructed by GO sheets and an oligopeptide possessed high drug-sustainability and on-demand drug release in vivo.…”
Section: 11mentioning
confidence: 99%
“…A long-term goal in material science is to learn from nature how to precisely control the properties of synthesised small organic molecules or macromolecules by self-assembly. Low-molecular weight oliogopeptides, inspired from the repeating units in proteins, are still of interest as organogelators (1)(2)(3). For instance, GAGA sequence, presented in silk protein as the repeating unit, forms antiparallel b-sheet structures by self-assembly (4 -6).…”
mentioning
confidence: 99%